Idiom-idiom Estetik Pastiche, Parodi, Kitsch, Camp, dan Skizofrenia dalam Karya Teater Postmodern Indonesia Jalan Lurus - Syafril Syafril (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2008)
Theater can be viewed as the strongest in denying post modernization. It also can be found in Indonesian postmodernism theater, especially through pastiche aesthetic idiom, parody, kitsch, camp, and schizophrenia which reveal and deconstruct the previous art theater modernization as well as the high culture modernization, or modernism itself. The purpose of this paper is to show how deconstructionist idiom occurs in the “Jalan Lurus” which can be viewed as one of Indonesian postmodern theaters. Keywords: theater, postmodern, pastiche, parody, kitsch camp, schizophrenia.